A continuum model of lithium ion transport inside graphene. (13th August 2018) - Chan, Yue; Wylie, Jonathan J.
Abstract: In this letter, we demonstrate the usage of a continuum equation in conjunction with Poisson equation and mean-field theory to investigate the ion transport and storage pattern of lithium ions between double-layer graphene. The majority of recent research on the ion transport for such batteries merely focuses on the effect of an external electric field acting on ions. Here, we emphasize the nanoscale mechanics of the graphene anode so that the forces between ions and the host material, and steric effects between lithium ions are incorporated. Under certain electric fields, multi-layers are formed between graphene sheets, and some related storage phenomenon is also investigated for potential applications in lithium ion battery and providing further understanding of ion transport inside biological channels.